2003
DOI: 10.1002/jctb.889
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic considerations on optimal design of a three‐phase airlift bioreactor with high solids loading

Abstract: The hydrodynamic study of a three-phase airlift (TPAL) bioreactor with an enlarged gas-liquid dual separator was carried out. Different lengths and diameters of the draft tube were tested to show how the design of the separator zone affects the hydrodynamic performance of the TPAL reactor. Ca-alginate beads with entrapped yeast biomass at different loadings (0, 7, 14 and 21% v/v) were used in order to mimic the solid phase of conventional high cell density systems, such as those with cells immobilized on carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 18 publications
3
15
0
6
Order By: Relevance
“…However, from Figure 4, it can be found that varepslon SR decreases bute SD increases with increasing J G . These results are similar to those reported by Klein et al [28].…”
Section: Effect Of Superficial Gas Velocity (J G )supporting
confidence: 83%
“…However, from Figure 4, it can be found that varepslon SR decreases bute SD increases with increasing J G . These results are similar to those reported by Klein et al [28].…”
Section: Effect Of Superficial Gas Velocity (J G )supporting
confidence: 83%
“…During the modeling, the bridge effect that addition of solids leads to a decrease in the flow channel has been taken into account. The similar effect was reported by Klein et al [15]. In order to balance the energy inputted and consumed in the circulation, a modified diameter of the separator tubes is introduced as:…”
Section: Energy Balance In the Separatormentioning
confidence: 52%
“…Because of the flow resis- tance increase with increasing solid holdup [14], the energy consumed by the flow increases and the liquid velocity decreases with increasing solid holdup. Klein et al [15] also found that the liquid velocity decreases with increasing solid holdup.…”
Section: Liquid Velocitymentioning
confidence: 93%
“…This is better seen at 250 mL/min than at 400 mL/min. In general the gas holdup in the riser of iGLR decreases in the presence of solids, being more significant at gas superficial velocities above 10 cm/s (Freitas and Teixeira, 1998;Klein et al, 2003). It is important to note that in three-phase iGLR there are a lot of different mechanisms that may influence gas holdup (design, type of solids and operational conditions) and the impact of each one of them is not yet clear (Chisti, 1989).…”
Section: Riser Gas Holdup In G-l-s Configurationsmentioning
confidence: 98%